2020
DOI: 10.21511/ppm.18(4).2020.10
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of sectoral contribution to regional divergence in Poland and Ukraine

Abstract: The research aims to identify industrial and other economic sectors’ contribution to the regional divergence in Eastern European countries, particularly Poland and Ukraine. The ambiguity of the results of previous studies on the factors of regional convergence indicates the need for further research, considering the peculiarities of distinct economies’ development. The countries selected for analysis – Ukraine and Poland – had similar starting conditions for market transformation, have a common border, and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Low perceptions of worthiness lead individuals to distance themselves from others to be less vulnerable in case of rejection (Harris & Orth, 2020). In the current war, 20% of those individuals who were displaced reported feelings of worthlessness (Deineko, 2022). This may be related to contextual factors such as access to adequate housing, basic services, socioeconomic opportunities, and community support (Tay, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Low perceptions of worthiness lead individuals to distance themselves from others to be less vulnerable in case of rejection (Harris & Orth, 2020). In the current war, 20% of those individuals who were displaced reported feelings of worthlessness (Deineko, 2022). This may be related to contextual factors such as access to adequate housing, basic services, socioeconomic opportunities, and community support (Tay, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Second, to identify the social cohesion shifts that occurred since the war started the article draws on the results of the nationwide survey 'War in Ukraine: a sociological survey' conducted by the same Dnipro-based Ukrainian company at the request of the NIBR OsloMet among the general population in mid-March 2022 (sample size 3007; the method used: telephone interviews). The questionnaire covered issues of relocation, current needs, resistance practices, and the psychological and emotional state of the populace (for details see Deineko 2022). We also draw on survey data gathered by 'Operatyvna Sociologiya' (July 27-30, 2022) via the Computer Assisted Web Interview (CAWI) method in the mobile application 'OperSo'.…”
Section: Methodsmentioning
confidence: 99%
“…People from different regions helped each other and hosted IDPs from the war zones, reoriented their businesses towards military and civil needs, and donated money to support the Armed Forces of Ukraine. The research survey 'War in Ukraine: a sociological survey' held in March 2022 revealed that only 16% of Ukrainians were not engaged in any type of volunteering (Deineko 2022). According to the correlation analysis, people tried to be effective in areas where they thought they had aptitude: women were more active in helping others and making monetary donations; men -in participating in territorial defense, institutionalized volunteering, conducting cyberattacks; the oldest -in non-formal volunteering.…”
Section: Bridging 'Horizontals': the New Quality Of Social Interactionsmentioning
confidence: 99%
“…It is worth considering a study aimed at determining the contribution of industry and other sectors of the economy to regional divergence in Eastern Europe, in particular, in Poland and Ukraine [6,7]. Regional inequalities in economic growth are observed in most countries and regions of some countries when studies focus on the peculiarities of convergence or divergence for the regions of Ukraine [8], as well as regional disparities in socio-economic development [9,10,11].…”
Section: Literature Reviewmentioning
confidence: 99%